THE DIFFERENCE BETWEEN INSTANTANEOUS AND PERMANENT INFRINGEMENTS: REGARDING THE INFRACTION TYPIFIED IN NUMERAL 66) OF ARTICLE 134 OF THE REGULATION OF THE GENERAL FISHERIES LAW - Cortez Jara, Luis Alberto (2019)
In this paper we analyze the difference between instantaneous and permanent administrative infractions, in light of article 252 of the Single Orderly Text of Law N° 27444, Law of General Administrative Procedure, approved by Supreme Decree N° 004-2019-JUS and the most approved doctrine; to then evaluate whether the infringement stipulated in the current numeral 66) of article 134 of the Regulations of the General Fishing Law, approved by Supreme Decree N° 012-2001-PE, amended by Supreme Decree N° 017-2017-PRODUCE, is an instantaneous infringement, as considered by the Sanctions Appeals Council of the Ministry of Production in Plenary Agreement N° 003-2017, by developing the legal nature of the same assumption of fact contained in the old infraction typified in numeral 101) of article 134 of the Regulations of the General Fishing Law, approved by Supreme Decree N° 012-2001-PE, modified by Supreme Decree N° 013-2009-PRODUCE, concluding that the Sanctions Appeals Council of the Ministry of Production is mistaken in considering the infraction in mention as instantaneous, because in fact is a permanent one.